2019
DOI: 10.1016/j.bbmt.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Glucocorticoid Prophylaxis on Chronic Graft-versus-Host Disease and Graft-versus-Host Disease–Free, Relapse-Free Survival after Haploidentical Transplantation: Long-Term Follow-Up of a Controlled, Randomized Open-Label Trial

Abstract: A B S T R A C TThis long-term follow-up study evaluated the effects of corticosteroid prophylaxis on graft-versus-host disease (GVHD)-free, relapse-free survival (GRFS) based on a controlled open-label randomized trial in which 228 allotransplant recipients were categorized as low risk (n = 83, group A) or high risk; patients at high risk were randomly assigned to receive (n = 72, group B) or not receive (n = 73, group C) low-dose methylprednisolone prophylaxis. The cumulative incidences of chronic GVHD, relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…However, it must be noted that both ATG and PTCy are associated with delayed immune reconstitution and increased risk of viral reactivation and serious infection 43–45 . Prospective studies have demonstrated that prophylactic use of low‐dose glucocorticoids in haplo‐HCT can successfully reduce the incidence of aGvHD and cGvHD without increasing the risk of infectious diseases and corticosteroid‐related complications 46,47 . Given that severe aGvHD is one of the main contributors to transplantation‐related mortality 18 and cGvHD is another contributor to secondary malignancy, 15,18 prospective randomised clinical trials are needed to develop a better algorithm of GvHD prophylaxis in patients with FA receiving unmanipulated haplo‐HCT.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that both ATG and PTCy are associated with delayed immune reconstitution and increased risk of viral reactivation and serious infection 43–45 . Prospective studies have demonstrated that prophylactic use of low‐dose glucocorticoids in haplo‐HCT can successfully reduce the incidence of aGvHD and cGvHD without increasing the risk of infectious diseases and corticosteroid‐related complications 46,47 . Given that severe aGvHD is one of the main contributors to transplantation‐related mortality 18 and cGvHD is another contributor to secondary malignancy, 15,18 prospective randomised clinical trials are needed to develop a better algorithm of GvHD prophylaxis in patients with FA receiving unmanipulated haplo‐HCT.…”
Section: Discussionmentioning
confidence: 99%
“…This work describes two patients with FA diagnosis taken to HSCT with reduced‐intensity conditioning and GvHD prophylaxis with an adapted dose of PTCy. Given our prior experience with three patients who received the protocol reported in the literature, 12,15 of which only one survived and has moderate chronic GvHD; and the remaining patients had severe mucositis and bacteremia, herein, it was decided to modify the protocol by increasing the ATG dose, keeping the pre‐HSCT radiotherapy dose on day −6, skipping the Cy dose in conditioning and administering an adjusted dose of PTCy, as well as changing MMF to MTX 16 in the GvHD prophylaxis and adding low‐dose steroid, 17 in accordance with that already published, seeking to reduce toxicity and GvHD (Table 2). Both patients in this report tolerated the procedure and had excellent outcomes, with an early 100% chimerism result, without severe infectious complications or severe GvHD, demonstrating a promising strategy for these patients and opening the panorama for new higher‐scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…La fotoresis extracorpórea (FEC) es una terapia inmunomoduladora atractiva que evita la inmunosupresión generalizada, siendo este el tratamiento de segunda línea refractario a esteroides. Es por esto que la FEC consiste en infundir linfocitos irradiados con radiación ultravioleta e incubarlos con 8 -metoxipsoraleno, para regular los clones de células T activos y aumentar las células T reguladoras; aunque el número de estudios publicados es limitado, se demuestra eficacia 17,18 .…”
Section: Tratamiento De Eichunclassified